Desentralisasi Penataan Ruang di Indonesia Pasca UU Cipta Kerja: Pergeseran Kewenangan, Dinamika Tata Kelola, dan Implikasinya terhadap Otonomi Daerah (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Policy reform through Law No. 11 of 2020 on Job Creation (the Omnibus Law) has significantly transformed the distribution of authority in spatial planning governance in Indonesia. This study analyzes the decentralization issues related to spatial planning authority following the enactment of the Omnibus Law, using a public policy and governance perspective. Drawing on theoretical reviews of decentralization, regional autonomy, and the national legal framework for spatial planning, this study identifies a shift toward centralization, marked by the strengthened role of the central government in planning, designation of strategic areas, and the implementation of a centralized, risk-based licensing system. While these reforms aim to improve licensing efficiency and policy coherence across jurisdictions, they also constrain local government authority, reduce public participation, and raise the potential for center–region conflicts. The findings highlight that the success of spatial planning reform depends on an institutional design that fosters synergy between the central government, regional authorities, and local communities. Accordingly, the study recommends enhancing consultation mechanisms between central and regional governments, ensuring meaningful public participation, introducing flexibility in the implementation of national standards, and strengthening local capacity and oversight. Effective spatial planning requires balancing national effectiveness with sensitivity to local characteristics, in support of sustainable and inclusive development.